2022
DOI: 10.1111/ggi.14381
|View full text |Cite
|
Sign up to set email alerts
|

Albumin/fibrinogen ratio, an independent risk factor for postoperative delirium after total joint arthroplasty

Abstract: Aim Postoperative delirium (POD) is a very common and serious complication after total joint arthroplasty (TJA), which is closely associated with many adverse consequences and a poor prognosis. This study aimed to establish the potential risk factors for POD. Methods In total, 336 patients who underwent elective TJA under general anesthesia between 2018 and 2021 were included and deemed eligible for inclusion. POD was diagnosed based on the criteria by the Diagnostic and Statistical Manual of Mental Disorders,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…After reading the titles and abstracts and excluding irrelevant literature, 45 articles were retained. After excluding duplicate studies and applying the inclusion criteria and exclusion criteria, 25 studies (Priner et al, 2008;Jankowski et al, 2011;Flink et al, 2012;Nandi et al, 2014;Chung et al, 2015;Wang et al, 2016Wang et al, , 2022Yen et al, 2016;Bosmak et al, 2017;Chen et al, 2017Chen et al, , 2021aCunningham et al, 2017Cunningham et al, , 2019Petersen et al, 2017;Aziz et al, 2018;Weinstein et al, 2018;Huang et al, 2019;Memtsoudis et al, 2019;Peng et al, 2019;He et al, 2020;Kijima et al, 2020;Qi et al, 2020;Jiang and Lei, 2022;Lin et al, 2022) including 3,767,761 patients from 9 countries were finally included. One study (Memtsoudis et al, 2019) separately reported the risk factors for delirium after TKA and THA.…”
Section: Literature Screening Process and Resultsmentioning
confidence: 99%
“…After reading the titles and abstracts and excluding irrelevant literature, 45 articles were retained. After excluding duplicate studies and applying the inclusion criteria and exclusion criteria, 25 studies (Priner et al, 2008;Jankowski et al, 2011;Flink et al, 2012;Nandi et al, 2014;Chung et al, 2015;Wang et al, 2016Wang et al, , 2022Yen et al, 2016;Bosmak et al, 2017;Chen et al, 2017Chen et al, , 2021aCunningham et al, 2017Cunningham et al, , 2019Petersen et al, 2017;Aziz et al, 2018;Weinstein et al, 2018;Huang et al, 2019;Memtsoudis et al, 2019;Peng et al, 2019;He et al, 2020;Kijima et al, 2020;Qi et al, 2020;Jiang and Lei, 2022;Lin et al, 2022) including 3,767,761 patients from 9 countries were finally included. One study (Memtsoudis et al, 2019) separately reported the risk factors for delirium after TKA and THA.…”
Section: Literature Screening Process and Resultsmentioning
confidence: 99%
“…In our study, functional analysis of the post-operatively dysregulated biomarkers suggests a system-wide activation of the inflammatory cascade and related immunological reactions. Data on the associations between delirium and acute-phase reactants (APR) such as CRP is ubiquitous [20,[44][45][46][47]. Although known APRs correlate well with the severity of inflammation, their usefulness as biomarkers is limited as they are not specific to delirium.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increasing age is also accompanied with the prevalence of frailty, which is more susceptible to POD [ 25 ]. A recent study by Jiang et al [ 26 ] indicates AFR as an independent risk factor for POD in elderly patients after total joint arthroplasty. In addition, a recent retrospective study suggests that NLR is an independent predictor of poststroke delirium among patients with acute ischemic stroke [ 16 ].…”
Section: Discussionmentioning
confidence: 99%